Empowering communities: asset-based approaches to community writing partnerships - Payne, Ania Sonora (Kansas State University, 2024)
The field of community engagement – and within that, the field of community writing – has been moving toward engagement practices that aim to empower communities by prioritizing community knowledge, building on communities’ assets, and creating collaborative, reciprocal partnerships. Although research in the field of community writing has led to many theories of “co-creation, mutuality, and reciprocity…community-based writing practitioners may still find it hard to put such theories into practice” (Knight, 2022, p. 6). Specifically, the field lacks research about the logistical, design, and curricular elements of service-learning experiences (Gilbride-Brown, 2011; Marby, 1998). In response, this work is comprised of three articles that aim to contribute towards that gap. Chapter 3 employs qualitative content analysis to uncover how community partners, partnerships, and community-engaged projects are described on English syllabi included on Campus Compact’s syllabi library. Chapter 4 uses framing analysis to review those same syllabi to understand the diagnostic, prognostic, and motivational frames that English instructors are using to describe community projects to their students. Chapter 5 argues that writing students can conduct an audience analysis rooted in appreciative inquiry at the onset of a community writing project to begin to learn about their community partners through their assets, rather than their deficits. The findings of the studies presented in Chapter 4 and Chapter 5 suggest that 1) English instructors use a wide range of terms to describe community projects and partners to their students, and often fail to connect this work to a course’s disciplinary goals and assigned texts and 2) although the field is aware of the danger of deficit-based language, deficit frames of communities still dominate the language that we use on our syllabi. Each chapter offers a series of recommendations that English instructors can use to elevate community partners’ unique strengths, both on course syllabi and in the classroom.
Keywords: Community engagement; Community writing; Writing studies; Community partnerships